Partial characterization of human complement factor H by protein and cDNA sequencing: Homology with other complement and non-complement proteins. Issue 1 (January 1986) - Ripoche, J.; Day, A. J.; Willis, A. C.; Belt, K. T.; Campbell, R. D.; Sim, R. B.
Abstract : Factor H, a control protein of the human complement system, is closely related in functional activity to two other complement control proteins, C4b-binding protein (C4bp) and complement receptor type 1 (CR1). C4bp is known to have an unusual primary structure consisting of eight homologous units each about 60 amino acids long. Such units also occur in the N-terminal regions of the complement proteins C2 and factor B, and in the non-complement serum glycoprotein β2 I. Amino acid sequencing, and sequencing of a factor H cDNA clone, show that factor H also contains internal repeating units, and is homologous to the proteins listed above.